Philippine alternative dispute resolution - Alogoc, Irene de Torres (Central Book Supply, Inc., 2021)
The features and advantages of ADR are widely discussed in extant literature and this book will undoubtedly touch on them extensively and expertly. These discussions tend to support the argument that ADR mechanisms are far better alternatives to the formalistic and lengthy court trials. This is true for the most part. ADR mechanisms improve on the formalistic and adversarial court processes, making possible the faster resolution of disputes and conflicts.